Premedication before intubation in UK neonatal units. Issue 1 (1st January 2000) - Whyte, Simon; Birrell, Ginny; Wyllie, Jonathan
Abstract : AIMS: To establish the extent and type of premedication used before intubation in neonatal units in the United Kingdom. METHODS: A structured telephone survey was conducted of 241 eligible units. Units were subdivided into those that routinely intubated and ventilated babies (routine group) and those that transferred intubated and ventilated babies (transfer group). RESULTS: Of the units contacted, 239 (99%) participated. Only 88/239 (37%) gave any sedation before intubating on the unit and only 34/239 (14%) had a written policy covering this. Morphine was used most commonly (66%), with other opioids and benzodiazepines used less frequently. Of the 88 units using sedation, 19 (22%) also used paralysis. Suxamethonium was given by 10/19 (53%) but only half of these combined it with atropine. Drug doses varied by factors of up to 200, even for commonly used drugs. CONCLUSION: Most UK neonatal units do not sedate babies before intubating, despite evidence of physiological and practical benefits. Only a minority have written guidelines, which prohibits auditing of practice.